2012
DOI: 10.1016/j.febslet.2012.03.049
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral benzodiazepine receptor regulates vascular endothelial activations via suppression of the voltage‐dependent anion channel‐1

Abstract: a b s t r a c tPeripheral benzodiazepine receptor (PBR) is a multifunctional protein mainly found on the outer mitochondrial membrane. PBR expression is increased by tumor necrosis factor-a (TNF-a) in endothelial cells. Adenoviral overexpression of PBR inhibits monocyte adhesion, VCAM-1, and ICAM-1 expression in TNF-a-activated endothelial cells. Rotenone, cyclosporine A, and bongkrekic acid suppress TNF-a-induced VCAM-1 expression. Overexpression of PBR inhibits voltage-dependent anion channel-1 (VDAC-1) expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…In addition, the reported grouping of TSPO molecules around VDAC, potentially reflecting TSPO polymerization [296,348], could enhance the concentration of ROS generated by TSPO in the proximity of VDAC, leading to apoptosis induction [296,349,350]. In addition, over-expression of TSPO inhibits VDAC1 expression, while the silencing of TSPO increases VDAC1 expression in endothelial cells [351]. PTP opening is regulated by different TSPO ligands, such as the agonist Ro5-4864 and the antagonist PK11195, as well as by the endogenous ligand protoporphyrin IX [352,353].…”
Section: Translocator Protein (Tspo) and Vdac1mentioning
confidence: 99%
“…In addition, the reported grouping of TSPO molecules around VDAC, potentially reflecting TSPO polymerization [296,348], could enhance the concentration of ROS generated by TSPO in the proximity of VDAC, leading to apoptosis induction [296,349,350]. In addition, over-expression of TSPO inhibits VDAC1 expression, while the silencing of TSPO increases VDAC1 expression in endothelial cells [351]. PTP opening is regulated by different TSPO ligands, such as the agonist Ro5-4864 and the antagonist PK11195, as well as by the endogenous ligand protoporphyrin IX [352,353].…”
Section: Translocator Protein (Tspo) and Vdac1mentioning
confidence: 99%
“…In addition, mammalian TSPOs can regulate the expression or stability of their interacting partner. For instance, overexpression of TSPO1 inhibits the expression of the mitochondrial voltage-dependent anion channel 1 (VDAC1), and the silencing of TSPO1 increases VDAC1 expression in endothelial cells (Joo et al, 2012). Mammalian TSPO can also regulate the expression of a noninteracting protein.…”
Section: Introductionmentioning
confidence: 99%
“…It was demonstrated that TSPO overexpression in cells induces mitochondrial ROS production, with a reverse trend observed after TSPO knockdown (Gatliff et al 2014). However, there exists contrasting evidence that TSPO overexpression could dampen mitochondrial ROS production through an identical VDAC-dependent mechanism (Joo et al 2012(Joo et al , 2015. Second, without the need for any protein interactions, it has been suggested …”
Section: Tspo As a Regulator Of Redox Homeostasismentioning
confidence: 99%
“…Therefore, it is possible that these interpretations may be confounded with cellular effects associated with the obvious link between stress and ROS production. The TSPO-VDAC relationship to ROS production has had contrasting results in similar TSPO overexpression studies (Gatliff et al 2014, Joo et al 2012. The TSPO-NOX2 association (Guilarte et al 2016), remains a hypothesis.…”
Section: :1mentioning
confidence: 99%
See 1 more Smart Citation